Resistance screening and influence of fruit physico-biochemical properties of "Carabao" and other mango varieties against oriental fruit fly, Bactrocera dorsalis (Diptera tephritidae), in the Philippines - Sison, Maria Luz J.; Cortaga, Cris Q.; Barcos, Ana Kristine S.; Laurel, Niño R.; Mateo, John Marty C.; dela Cueva, Fe M. (2020)
The Philippines is one of the major exporters of fresh and dried mangoes in the world, with "Carabao" (Mangifera indica L.) as its flagship variety. Among the most damaging pests that attack this cultivar is the oriental fruit fly, Bactrocera dorsalis Hendel, which limits the country's export potential drastically. The control and management of this pest have been developed; however, the search and use of resistant cultivars have not been explored in the Philippines. In this study, a total of 33 mango accessions consisting of ?Carabao? and other varieties were evaluated for resistance against B. dorsalis over a period of four years (one trial per year) through ?choice? tests. Repeated trials showed that accessions 12-209 ("Carabao"- Tree 203), 12-127 ("Carabao"- Tree 30), 12-103 ("Farrales"), and 16-010 (GES 77 NSIC Carabao variety) exhibited promising resistance ratings (i.e. no damage to moderately susceptible) against oriental fruit fly. Overall correlation analysis of fruit physico-biochemical properties revealed that insect visit is moderately affected by flesh flavonoid content. Meanwhile, adult emergence correlated to peel physicobiochemical properties, especially peel firmness, which considerably affected insect reproduction. Comparison between the most resistant and most susceptible accessions suggests that, apart from high flesh flavonoids and peel firmness, high flesh phenolics and low pH (acidic) levels may also play a defensive role in mango against oriental fruit fly. The accessions characterized can be used as stop-gap varieties or as parental lines for the breeding of resistant "Carabao" mango.